2015
DOI: 10.1007/s10896-015-9727-5
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Exposure to Intimate Partner Violence and Early Delinquency

Abstract: Children who experience trauma due to exposure to intimate partner violence (IPV) have been shown to exhibit higher than average rates of cognitive, psychological, and emotional impairments. Our research uses the first five waves of the Fragile Families and Child Well-being Study to examine the effects of exposure to intimate partner violence in early childhood (as measured by their mothers' experiences with physical violence and economic abuse) on delinquency at age nine . It also investigates whether these e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
32
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 57 publications
5
32
1
2
Order By: Relevance
“…As a result, traumatic experiences overwhelm the victims, disrupt their inner schemas about safety and trust, and strip them of control, connection, and meaning in life. Empirical studies have provided evidence that ACEs are traumatizing events that have extensive harmful and long-term consequences on mental health such as increasing likelihood of depression (McLaughlin et al, 2012 ; Weder et al, 2014 ; Merrick et al, 2017 ), on physical health and risky behaviors such as substance use and delinquency (Herrenkohl et al, 2013 ; Huang et al, 2015 ; Mandavia et al, 2016 ), as well as on life satisfaction and well-being (McElroy and Hevey, 2014 ; Mosley-Johnson et al, 2019 ). Echoing Herman's ( 1992 ) conjecture that trauma may leave victims without any connection or meaning in life, increased mental health problems, such as depression, may lead to diminished passion in life.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, traumatic experiences overwhelm the victims, disrupt their inner schemas about safety and trust, and strip them of control, connection, and meaning in life. Empirical studies have provided evidence that ACEs are traumatizing events that have extensive harmful and long-term consequences on mental health such as increasing likelihood of depression (McLaughlin et al, 2012 ; Weder et al, 2014 ; Merrick et al, 2017 ), on physical health and risky behaviors such as substance use and delinquency (Herrenkohl et al, 2013 ; Huang et al, 2015 ; Mandavia et al, 2016 ), as well as on life satisfaction and well-being (McElroy and Hevey, 2014 ; Mosley-Johnson et al, 2019 ). Echoing Herman's ( 1992 ) conjecture that trauma may leave victims without any connection or meaning in life, increased mental health problems, such as depression, may lead to diminished passion in life.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have reported a substantially increased risk for physically abusive parenting among mothers within domestically violent families, with rates ranging from 11–46% (for a review, see Jouriles, McDonald, Slep, Heyman, & Garrido, 2008). In a longitudinal study, Huang and colleagues (2015) found a dose effect such that the more physical violence the mothers experienced when the child was a toddler, the more likely they were to engage in physical punishment of the child at 5 years of age. Although less frequently examined within this context, other forms of compromised parenting – including neglectful, rejecting, harsh, and psychologically aggressive parenting – are also more prevalent among mothers of children (from preschool through adolescence) who have experienced physical IPV (Banyard, Williams, & Siegel, 2003; Gustafsson, Cox, & Blair, 2012; Huang et al, 2015; Kelleher et al, 2008; Olaya et al, 2010), and are likewise associated with poor outcomes for children (de la Vega, de la Osa, Granero, & Ezpeleta, 2013; Schwerdtfeger, Larzelere, Werner, Peters, & Oliver, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It is widely known that trauma is a pathway for youth, and particularly girls, to become involved in the JJ system (Chesney‐Lind & Shelden, 2004; Finkelhor, Turner, Ormrod, Hamby, & Kracke, 2017; Huang, Vikse, Lu, & Yi, 2015; Ko et al, 2008; Sharma, 2010; Winn, 2010) and the link between trauma and felony arrest is strongest for Black youth (Johnson, 2018). Histories of trauma and bootstrapping are associated with girls becoming involved in the JJ system and having deeper involvement in the JJ system for lower level offenses, a system which fails to address their trauma and exacerbates their symptoms (Espinosa et al, 2013; Flocks, Calvin, Chriss, & Prado‐Steiman, 2017; Jones, 2010; Simkins et al, 2004).…”
Section: Jdcs Are Not Suited For Girls’ Needsmentioning
confidence: 99%